Psychological resources as predictors of emotional and behavioral issues in young University students - Rivera Heredia, María Elena (2021)
Introduction: Preventing problem behaviors in university students requires the identification of its causes and possible protective factors. Objective: To identify the psychological resources that can predict emotional and behavioral issues in young people. Method: Four different scales were used to evaluate a non-probabilistic sample of 320 university students: the emotional and behavioral issues scales, the intra-family relationships scale, and the social resources scale and affective resources scale. The sample included 146 men and 173 women between the ages of 18 to 24 (mean: 20.04, standard deviation: 1.62). Results: The main findings show significant statistical negative correlations between the problem behaviors and the affective, social, and family resources. Regarding the differences between participants, women showed higher mean scores of depressions and somatic problems, while men showed higher scores of alcohols and tobacco consumption. The step-by-step regression results revealed depression to be the problem behavior with the highest explained variance (47%), predicted by difficulties in managing sadness, lack of self-control regarding anger, the expression of emotions, and problems with anger management. Conclusion: Strengthening psychological resources and incorporating them in the design of universal and selective intervention programs is fundamental to prevent emotional and behavioral problems in university students to promote their positive development.